Efectos de la nodulación en soja (Glycine max) - Rosas, G. S.; Oliva, C. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
In tests made in Pergamino, Argentina, it was found that nodulation in soybeans was conditioned to soil fertility. In fertile soil, seed yields, oil content of seeds, oil and protein yield per hectare, and quantity of fodder, did not differ from the controls. A greater concentration of inoculum had a negative effect on nodulation in fertile soil